Effect of hydrocolloids on the properties of wheat/potato starch mixtures - Varela, María Soledad; Navarro, Alba Sofia del Rosario; Yamul, Diego Karim (Wiley, 2019)
The physicochemical, pasting, thermal, viscoelastic, and syneresis properties of nine formulations prepared with wheat starch, potato starch, and hydrocolloids (pectin, HPMC, arabic gum, and konjac glucomannan (KG)) were assessed. The addition of the hydrocolloids decreased the water solubility index and water absorption capacity but did not modify the swelling power of starch granules. The starch gelatinization temperature decreased in the presence of the hydrocolloids, while the enthalpy of gelatinization and gelatinization range temperature increased. Pectin and HPMC addition decreased the paste viscosity whereas KG increased and arabic gum had no effect. On the other hand, the pasting temperature was not modified by the presence of hydrocolloids. All the blends behaved as solid as the storage modulus was higher than the viscous modulus within all the frequency range assayed. Viscous characteristics were improved with the addition of pectin and HPMC. The presence of hydrocolloids increased the stability of the gelled starch mixtures to freeze–thaw cycle and no syneresis was observed in these gels stored at 4°C.